2009
DOI: 10.2133/dmpk.24.458
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Influence of Concomitant Administration of Rabeprazole on the Pharmacokinetics of Tacrolimus in Adult Living-donor Liver Transplant Patients: A Case–control Study

Abstract: This study assesses the effects of rabeprazole on the pharmacokinetics of tacrolimus, considering the cytochrome P450 (CYP) 2C19 and CYP3A5 genotypes of living-donor liver transplant patients (native intestine) and their corresponding donors (graft liver). We examined the concentration/dose ratio of tacrolimus in transplant patients treated with (n=17) or without (n=38) rabeprazole at 10 mg/day on postoperative days 22-28. A stratified analysis revealed no significant differences between the control and rabepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In this respect, the elevation of tacrolimus levels when it is administered concomitantly with omeprazole in patients with CYP2C19*2/*2 had previously been described in liver recipients (Hosohata et al, 2008;Hosohata et al, 2009a;Hosohata et al, 2009b) and in healthy volunteers and renal recipients Takahashi et al, 2007;Maguire et al, 2012). However, no clinical relevance of this elevation has been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this respect, the elevation of tacrolimus levels when it is administered concomitantly with omeprazole in patients with CYP2C19*2/*2 had previously been described in liver recipients (Hosohata et al, 2008;Hosohata et al, 2009a;Hosohata et al, 2009b) and in healthy volunteers and renal recipients Takahashi et al, 2007;Maguire et al, 2012). However, no clinical relevance of this elevation has been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 83%
“…The decreasing effects of CYP3A5 expressers could hide the hypothetical increasing effect of CYP2C19*2/*2 genotype because of the described omeprazole-tacrolimus interaction. This is the reason why we decided to plot tacrolimus levels with regard to CYP2C19 only in the subset of patients with CYP3A5*3/*3s, as other authors have previously done (Hosohata et al, 2009a;Hosohata et al, 2009b). There is a work (Katsakiori et al, 2010) in which no elevation of tacrolimus levels was found in patients cotreated with omeprazole, but this was probably because the authors only considered CYP3A5 genotype and not CYP2C19; thus, they could not see the interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Uesugi et al showed that the CYP3A5 genotype in the graft liver and native intestine had an effect on the blood concentration of tacrolimus. 25) TVR inhibits not only CYP3A4 but also CYP3A5.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in many cases extended resections, which are substantially affected by the risk of postoperative liver failure, are needed to improve the curative rates. Therefore, optimization of postoperative outcome could increase the donor pool in LDLT and enable more extended anatomic and nonanatomic resections [24,25]. …”
Section: Discussionmentioning
confidence: 99%